1998
DOI: 10.1254/jjp.77.99
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Diameter Increase Induced by a Phosphodiesterase 5 Inhibitor, E4021, in Conscious Pigs

Abstract: The effects of intravenous infusions of 1, 3 and 10 microg/kg/min of the phosphodiesterase 5 inhibitor, E4021, at 30-min intervals on coronary artery diameter were studied in 8 conscious pigs monitored with a pair of piezoelectric crystals. The highest dose increased the diameter by 2.9 +/-0.5% (P <0.01 vs vehicle) of the baseline diameter, with a significant decrease in mean pulmonary arterial pressure. However, there were no changes in mean aortic pressure and heart rate. Additionally, E4021 significantly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…PDE isoenzymes in vascular smooth muscle. Previous studies using the PDE5 inhibitors zaprinast (23) or E4021 (29) demonstrated an increase in cGMP levels in isolated coronary artery segments and dose-dependent dilation of the large epicardial coronary arteries in awake pigs (1,29). Similarly, Wallis and co-workers (36) reported that sildenafil resulted in a significant increase of cGMP concentration in isolated canine coronary artery segments in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…PDE isoenzymes in vascular smooth muscle. Previous studies using the PDE5 inhibitors zaprinast (23) or E4021 (29) demonstrated an increase in cGMP levels in isolated coronary artery segments and dose-dependent dilation of the large epicardial coronary arteries in awake pigs (1,29). Similarly, Wallis and co-workers (36) reported that sildenafil resulted in a significant increase of cGMP concentration in isolated canine coronary artery segments in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…cGMP-mediated vasodilation occurs preferentially in arterial vessels with less effect at the level of the coronary arterioles (9). Selective inhibition of PDE5 with sildenafil (29), E4021 (1,20), or zaprinast (17) significantly increased cGMP and caused relaxation of isolated normal epicardial coronary arteries. In normal animals, stimulation of endogenous coronary NO production with acetylcholine (13), intraarterial infusion of NO donors (7,11), or intraarterial infusions of ANP or BNP resulted in resistance vessel dilation with an increase of coronary blood flow (14,29).…”
Section: Discussionmentioning
confidence: 99%
“…However, their use is limited due to their non-selective activity. Recently, highly selective intracellular PDE5 inhibitors (E4021, SCH 51866) were introduced in clinical trials to control hypertension, pulmonary hypertension, respiratory distress, platelet aggregation and erectile dysfunction [156][157][158][159][160][161][162][163][164]. Increased 3', 5' cGMP in the cerebral arterial wall by selective inhibition of PDE5 may prevent development of delayed vasospasm after SAH [165,166].…”
Section: Prevention Of Vasospasm By Pde Selective Inhibitormentioning
confidence: 99%